Public Service Strategy in Human and Community Development Planning at the Regional Development Planning Agency of North Halmahera Regency - Marsela Kondihi (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
Regional government performance planning serves as a fundamental instrument for the formulation of development programs, budgeting, implementation, and evaluation of public policies at the local level. This study aims to analyze the implementation of performance planning at the Regional Development Planning Agency (BAPPEDA) of North Halmahera Regency and to identify factors influencing its effectiveness in supporting regional development objectives. The research employs a descriptive qualitative approach, focusing on the performance planning process, alignment between organizational goals and strategic planning documents, the formulation of performance indicators, and institutional challenges encountered during implementation. Data were collected through interviews, document analysis, and direct observation of planning practices. The findings indicate that the implementation of performance planning has generally complied with prevailing regulatory frameworks and administrative procedures, particularly in the preparation of key planning documents such as the RPJMD, RKPD, strategic plans, and annual work plans. However, its effectiveness remains constrained by several factors, including limited work facilities and infrastructure, inadequate integration of development data, and suboptimal employee discipline and organizational commitment. These challenges affect the quality and timeliness of planning documents, ultimately influencing the achievement of institutional performance targets. The study concludes that effective performance planning is essential for enhancing governance quality and ensuring successful regional development. Strengthening institutional capacity, improving data integration systems, and fostering organizational discipline are necessary strategies to optimize planning performance and public sector accountability.